Minimally Invasive Intra-Calcaneal Fractures vs Conservative Treatment: A Propensity Score Matched Cohort Series. Issue 4 (November 2022) - Reichert, Ines; Ahluwalia, Raju S.; Musabahi, Omar; Lyle, Shirley
Category: Trauma; Hindfoot Introduction/Purpose: We prospectively assessed the impact of minimally invasive internal fixation of displaced intra-articular calcaneal fractures (DIACF) results in better health outcomes up to 2 years post- injury than non-operative management. Methods: All isolated calcaneal fractures were reviewed and the decision to treat was made by a multidisciplinary meeting. Operative-treatment protocol involved sinus-tarsi approach or per-cutaneous reduction & internal fixation under the care of a fellowship-trained-foot and ankle surgeon. Non-operative protocol involved symptomatic management with no attempt at closed reduction. All fractures were classified, and the MOXFQ/EQ5D-L scores were used to assess general and disease-specific outcomes respectively. Secondary outcome measures included return to work and return to leisure activity levels. Statistical analysis was performed to assess normality of data (Shapiro Wilk test/Q-Q plots). Propensity matching was conducted using nearest neighbour matching, followed by regression analysis and modelling to compare baseline covariates between the two different groups. Results: Between 2015-2019 total of 93 patients met the inclusion criteria. After propensity score matching 44 patients were found in the surgical/ treatment group. The mean age was 40 (vs. 43.3) in the surgical group, no significant difference in age, sex, peripheral vascular disease, smoking status, laterality, and baseline Bohlers and Guisane angle in the propensity score matched sample. The surgically treated group had a higher Sanders class(p<0.05), higher MOXFQ at 12 months (p<0.05) and EQ-5DL scores at 24 months(p<0.05) and were more likely to return to work at 12m (95% vs 77%)(p<0.05), and physical activity levels at 12m (57% vs 36%)(p=0.054). The wound complication rate was 14.8%, no patients required further surgery; whilst non-operative- treatment mandated surgery for arthritis (6), and or/an injection (7 vs.3). Conclusion: Both non-operative and operative treatments are valid in DIACF. MIS-surgery offers better functional outcomes for severer injury patterns, and a less-likely need for arthritis intervention at 2yrs.